Effects of voltage perturbation of the lingual receptive field on chorda tympani responses to Na+ and K+ salts in the rat: implications for gustatory transduction (The Rockefeller University Press, 1994)
Taste sensory responses from the chorda tympani nerve of the rat were recorded with the lingual receptive field under current or voltage clamp. Consistent with previous results (Ye, Q., G. L. Heck, and J. A. DeSimone. 1993. Journal of Neurophysiology. 70:167-178), responses to NaCl were highly sensitive to lingual voltage clamp condition. This can be attributed to changes in the electrochemical driving force for Na+ ions through apical membrane transducer channels in taste cells. In contrast, responses to KCl over the concentration range 50-500 mM were insensitive to the voltage clamp condition of the receptive field. These results indicate the absence of K+ conductances comparable to those for Na+ in the apical membranes of taste cells. This was supported by the strong anion dependence of K salt responses. At zero current clamp, the potassium gluconate (KGlu) threshold was > 250 mM, and onset kinetics were slow (12 s to reach half-maximal response). Faster onset kinetics and larger responses to KGlu occurred at negative voltage clamp (-50 mV). This indicates that when K+ ion is transported as a current, and thereby uncoupled from gluconate mobility, its rate of delivery to the K+ taste transducer increases. Analysis of conductances shows that the paracellular pathway in the lingual epithelium is 28 times more permeable to KCl than to KGlu. Responses to KGlu under negative voltage clamp were not affected by agents that are K+ channel blockers in other systems. The results indicate that K salt taste transduction is under paracellular diffusion control, which limits chemoreception efficiency. We conclude that rat K salt taste occurs by means of a subtight junctional transducer for K+ ions with access limited by anion mobility. The data suggest that this transducer is not cation selective which also accounts for the voltage and amiloride insensitive part of the response to NaCl.